Indonesia Systematic Country Diagnostic : Connecting the Bottom 40 Percent to the Prosperity Generation - World Bank Group (World Bank, Washington, DC, 2015)
The systematic country diagnostic (SCD) is designed to identify the most critical binding constraints and opportunities facing Indonesia in ending extreme poverty and boosting shared prosperity. In line with the World Bank Group’s (WBG’s) new country engagement model, the findings of the SCD will provide inputs for the preparation of the country partnership framework (CPF), which will outline the WBG’s engagement with Indonesia to achieve the twin goals. This SCD has four main conceptual elements. First, analyze past trends in growth, poverty, and inequality to highlight the deep drivers. Second, identify the key channels for reducing poverty and boosting the prosperity of the Bottom 40 percent. Third, highlight the major challenges and opportunities along each of the key channels, and finally identify prioritized areas of intervention to accelerate progress toward ending extreme poverty and boosting shared prosperity for each of the channels identified.